Komparasi Efektivitas Model Pembelajaran NHT dan STAD Ditinjau dari Hasil Belajar Pembelajaran Tematik Terpadu Siswa SD - Herianus Erwin; Nyoto Harjono (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to examine the differences in effectiveness between the Numbered Head Together (NHT) and Student Achievement Division (STAD) learning models in terms of the learning outcomes of integrated thematic learning in elementary schools. This study uses a meta-analysis method. Research data in the form of previous research results that are relevant to the research problem and obtained through Google Scolar. From the results of googling, each model obtained 10 articles that are in accordance with the research to be carried out. The results of the comparison of the two models prove that the average value achieved through the NHT learning model is 21.06%, while the STAD model is 20.63%. The results of the prerequisite test for the data of each model show Partial Eat Square is 0.308 with sig. 0.044, which means that the two models have a moderate effect on improving learning outcomes, while from the average results of increasing the value of learning outcomes, the NHT model is slightly more effective than the STAD model.